BAF45D Downregulation in Spinal Cord Ependymal Cells Following Spinal Cord Injury in Adult Rats and Its Potential Role in the Development of Neuronal Lesions - Wang, Zhenzhen; Huang, Jian; Liu, Chang; Liu, Lihua; Shen, Yuxian; Shen, Cailiang; Liu, Chao (Frontiers in Neuroscience, 2019)
The endogenous spinal cord ependymal cells (SCECs), which form the central canal (CC), are critically involved in proliferation, differentiation and migration after spinal cord injury (SCI) and represents a repair cell source in treating SCI. Previously, we reported that BAF45D is expressed in the SCECs and the spinal cord neurons in adult mice and knockdown of BAF45D fail to induce expression of PAX6, a neurogenic fate determinant, during early neural differentiation of human embryonic stem cells. However, the effects of SCI on expression of BAF45D have not been reported. The aim of this study is to explore the expression and potential role of BAF45D in rat SCI model. In this study, adult rats were randomly divided into intact, sham and SCI groups. We first explored expression of BAF45D in the SCECs in intact adult rats. We then explored SCI-induced loss of motor neurons and lesion of neurites in the anterior horns induced by the SCI. We also investigated whether the SCI-induced lesions in SCECs are accompanied by the motor neuron lesions. Finally, we examined the effect of BAF45D knockdown on cell growth in neuro2a cells. Our data showed that BAF45D is expressed in SCECs, neurons and oligodendrocytes but not astrocytes in the spinal cords of intact adult rats. After SCI, the structure of CC was disrupted and the BAF45D-positive SCEC-derivatives were decreased. During the early stages of SCI, when shape of CC was affected but there was no disruption in circular structure of the SCECs, it was evident that there was a significant reduction in the number of neurites and motor neurons in the anterior horns compared with those of intact rats. In comparison, a complete loss of SCECs accompanied by further loss of motor neurons but not neurites was observed at the later stage. BAF45D knockdown was also found to inhibit cell growth in neuro2a cells. These results highlight the decreased expression of BAF45D in SCI-injured SCECs and the potential role of BAF45D downregulation in development of neuronal lesion after SCI in adult rats.